2015
DOI: 10.1515/eec-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Natura 2000 Network in Poland – an Opportunity or a Threat to Sustainable Development of Rural Areas? Study on Local Stakeholders’ Perception1

Abstract: Conflicts related to the implementation of the Natura 2000 network can be found in Poland and other European countries. The general causes of those conflicts are known. Some of them lie in the habitat directive itself, and others are related to the transposition of the directive into national environmental law and management systems. The designation of Natura 2000 sites in Poland involved strong protests on a local level, mainly due to the lack of consultations with the stakeholders, or at least with the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Participation space occurs through formal and non-formal mechanisms. This forum is useful for encouraging participatory development, thereby creating inclusivity in development (Chmielewski & Głogowska, 2015). The Bahu Palawa Village Government carries out participation forums where the community is given space to get involved in the development process of the village tourism sector.…”
Section: Discussion: Social Inclusion Empowerment and Barriers To Dev...mentioning
confidence: 99%
See 1 more Smart Citation
“…Participation space occurs through formal and non-formal mechanisms. This forum is useful for encouraging participatory development, thereby creating inclusivity in development (Chmielewski & Głogowska, 2015). The Bahu Palawa Village Government carries out participation forums where the community is given space to get involved in the development process of the village tourism sector.…”
Section: Discussion: Social Inclusion Empowerment and Barriers To Dev...mentioning
confidence: 99%
“…First, existing research discusses local development by examining the development of alternatives tourism (Abellán & García Martínez, 2021;Molpeceres et al, 2021;Ossowska et al, 2023), inequality (Mantino, 2022), and the relationship between agriculture and tourism in rural areas (Bartkowiak-Bakun et al, 2020). Second, previous research tends to discuss rural development by focusing on aspects of sustainable development (Ancuța & Jucu, 2023;Berrueta et al, 2017;Chmielewski & Głogowska, 2015;Dumitru et al, 2021;Wolny et al, 2019). Third, previous research tends to focus on developing local wisdom (Ayu Saraswati Bhakti & Iskandar, 2020;Cerquetti et al, 2022;Lin et al, 2022;Pourzakarya, 2022;Šťastná et al, 2020) to become a source of village economy.…”
Section: Introductionmentioning
confidence: 99%
“…In both those studies, the role and weight of local stakeholders, e.g., municipalities and landowners, is emphasized as an "ingredient" for the public acceptance of nature conservation policies. Chmielewski and Głogowska [21] focused on the conflicts related to information and communication technologies in randomly selected Natura 2000 sites in Poland. Those authors showed that from the perspective of local stakeholders, the Natura 2000 sites are an opportunity for sustainable regional development.…”
Section: Introductionmentioning
confidence: 99%
“…Following this trend, the protected areas of the Natura 2000 network include the Spanish and Basque community (Hoyos et al 2015) as well as the Polish one (Pietrzyk-Kaszyńska et al 2012;Chmielewski & Głogowska 2015), alongside the Romanian one (website 4). For example, protected areas are indicated as areas contested by small farmers or Ethiopian shepherds, challenging the boundaries of a national park, land use and the involvement of local people in the act of good management (Kelboro and Stellmacher 2015).…”
Section: Introductionmentioning
confidence: 99%